NMDA receptor and nitric oxide synthase activity in the central amygdala is involved in the acquisition and consolidation of conditioned odor aversion. (10th August 2019) - González-Sánchez, Héctor; Tovar-Díaz, Jorge; Morin, Jean-Pascal; Roldán-Roldán, Gabriel
Highlights: NMDA receptors activity in the Central Amygdala is required for Acquisition of Conditioned Odor Aversion. NMDA receptors activity is required for up to 15 min after conditioning for Long-term odor aversion Memory formation. Nitric Oxide Synthase activity is required for both acquisition and consolidation of Conditioned Odor Aversion. Neither NMDA receptors nor Nitric Oxide Synthase activity is necessary for aversion memory retrieval. Abstract: Rats readily learn to avoid a tasteless odorized solution if they experience visceral malaise after consuming it. This phenomenon is referred to as conditioned odor aversion (COA). Several studies have shown that COA depends on the functional integrity of the amygdala, with most studies focusing on the basolateral nucleus. On the other hand, the role of the central amygdala (CeA) which is known to be involved in the consolidation of conditioned taste aversion (CTA) remains to be established. To address this issue, we evaluated the effect of inhibiting NMDA receptor activity in this structure on COA memory formation. Intra-CeA infusions of non-competitive NMDA receptor inhibitor MK-801 prevented memory formation both when administered before and up to 15 min after COA conditioning, while no effect of this drug was observed when given before long-term memory test. We next evaluated the role of one of the main downstream effectors of brain NMDA receptor signaling, nitric oxide synthase (NOS), known to play a key role in a wide variety learning tasks including some types of olfactory conditioning. Similar results were obtained with inhibition of either NOS or neuron-specific NOS; which proved to be required both during and after COA training, though for a shorter time span than NMDA receptors. Also, neither isoform showed to be required to memory retrieval. These results suggest that the US signaling during acquisition and the initial consolidation step of COA depends on glutamate-NO system activation in the CeA.